Ablação cirúrgica dos bulbos olfatórios em coelhos: modelo para estudos de patogenia de infecções por vírus neurotrópicos - Fonseca, Erika Toledo da (2006)
Rabbits have been used as animal models to study the pathogenesis of neurological infection by bovine herpesvirus type 5 (BHV-5), an important agent of meningoencephalitis in cattle. The olfactory system has been implicated as the main pathway for the virus to reach the brain after replication in the nasal mucosa. To investigate the role of the olfactory route in the pathogenesis of neurological infection, a technique of transfrontal craniotomy for ablation of the main olfactory bulbs (MOBs), using the eyes as the anatomic reference was developed and evaluated. Using this technique, twenty three 30 days-old rabbits were submitted to surgical ablation of the MOBs and subsequently inoculated with BHV-5. After skin, subcutaneous tissue and periosteum incisions, the craniotomy was performed in a point equidistant to the medial corner of the eyes, with a 3 mm drill coupled to a low intensity elyptic drilling machine. The removal of the MOB s tissue was performed by using a number 6 uretral probe coupled to a surgical vaccum pump. The anatomic references used were appropriate in allowing an adequate and easy access to the MOBs. Necropsy performed in three animals after the surgery demonstrated that the surgical procedure was efficient in completely removing the MOB tissue. This was also demonstrated by the interruption of the access of the virus to the brain after intranasal inoculation: only one animal (1/11) in the bulbectomized group developed neurological infection and disease, against 100% (10/10) of the control group. The transfrontal craniotomy using the eyes as the anatomical reference allowed for an adequate access for localization and removal of the MOBs in rabbits. This techique may be used in studies of viral pathogenesis requiring the complete interruption of the olfactory connection to the brain.